Reduced graphene oxide-templated photochemical synthesis and in situ assembly of Au nanodots to orderly patterned Au nanodot chains - Wei, Yanyan (2012)
A novel photochemical method for the synthesis of fluorescent Au nanodots (size ≈1.2nm) is proposed (see image). The results clearly demonstrate that reduced graphene oxide sheets modified with functional organic molecules can be used as templates for the synthesis and in situ assembly of metal nanostructures, thus opening up new possibilities for future graphene-based chemical synthesis.